2003
DOI: 10.1111/1467-6494.7106007
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Conflict, Agreeableness, and Personality Development

Abstract: This multimethod research linked the Big-Five personality dimensions to interpersonal conflict in childhood. Agreeableness was the personality dimension of focus because this dimension has been associated with maintaining positive interpersonal relations in adolescents and adults. In two studies, elementary school children were assessed on the Big-Five domains of personality. Study 1 (n=276) showed that agreeableness was uniquely associated with endorsements of conflict resolution tactics in children as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
80
2
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(97 citation statements)
references
References 51 publications
11
80
2
4
Order By: Relevance
“…In addition, the meta-analytic findings that some personality variables appeared to predict one of two patterns of aggressive behavior are in consonance with previous findings (e.g., Graziano et al, 1996;Jensen-Campbell et al, 2003;R. Martin et al, 2000) that have shown positive correlations between these personality dimensions and self-reported aggression.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the meta-analytic findings that some personality variables appeared to predict one of two patterns of aggressive behavior are in consonance with previous findings (e.g., Graziano et al, 1996;Jensen-Campbell et al, 2003;R. Martin et al, 2000) that have shown positive correlations between these personality dimensions and self-reported aggression.…”
Section: Discussionsupporting
confidence: 90%
“…The role of agreeableness in mediating the behavior of an individual in interpersonal relationships has already been evidenced in studies from various populations, showing that individuals who score low on this trait tend to overtly express their angry emotions whereas those with higher agreeableness are calmer, more cooperative, more skilled in solving interpersonal conflicts and, when coping with stress, they are more eager to seek social support [4,18]. Some studies in other chronically ill patients showed that agreeableness interacted with social support in affecting depressive symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…Dengan kata lain, konflik berlaku akibat daripada perbezaan matlamat, nilai dan persepsi sehingga memberikan kesan negatif. Dalam percakapan, konflik dijangkakan berlaku apabila kanak-kanak, remaja atau orang dewasa bertentangan pendapat antara satu sama lain (Jensen-Campbell, Gleason & Malcolm 2003).…”
Section: Pengenalanunclassified